An ab initio study of the reaction mechanism of 2-methylbenzaldehyde acetalization with methanol - Muhammad Yusuf; Ahmad Kamil Nasution (Pascasarjana Universitas Negeri Medan, 2022)
Acetalization of 2-methylbenzaldehyde is a type of reaction that occur by reacting 2-methylbenzaldehyde with methanol. Meanwhile, the catalyst used in the reaction is an acid catalyst. This research was conducted to determine the pathway of the intermediate reaction mechanism that is most likely to produce 2-methylbenzaldehyde acetal product. The software used in this research is HyperChem 8.0, 6-31G* basis sets, with the ab initio method. Before being calculated, the molecular structure is drawn with a 2-dimensional view. After that, the molecular structure is converted into a 3D view and geometry optimization is carried out. The results obtained are in the form of optimized energy from the structure of reactant 2-methylbenzaldehyde, several intermediate products, and product 2-methylbenzaldehyde acetal.Keywords:Ab initio, Acetal, 2-methylbenzaldehyde, Reaction mechanism